UKURAN PERUSAHAAN, PROFITABILITAS, POLITICAL COST, TIPE INDUSTRI, DAN KINERJA LINGKUNGAN TERHADAP ENVIRONMENTAL DISCLOSURE - Melda Yanti Siregar; Indra Kusumawardhani (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2023)
Environmental disclosure is the disclosure of information related to the environment in the company's annual report and sustainability report. Research related to environmental disclosure is developing quite rapidly, but still produces various findings. This study aims to determine and examine the effect of company size, profitability, political costs, type of industry and environmental performance on environmental disclosure. The population in this study are non-financial public companies listed on the Indonesia Stock Exchange (IDX) and registered as PROPER participants for 2017-2021. The sampling method in this study used a purposive sampling technique. The unit of analysis is the annual report, corporate sustainability report and list of PROPER participants for 2017-2021, totaling 177 population. The data analysis method used is multiple linear regression analysis. The test results show that profitability and environmental performance have a positive effect on environmental disclosure. However, company size, political costs and type of industry have no effect on environmental disclosure.